2022
DOI: 10.7759/cureus.30426
|View full text |Cite
|
Sign up to set email alerts
|

Attitude and Perception Toward Taking Selfies and Using Filters and Their Relationship With Blepharoplasty

Abstract: Background: Due to the general increase in the use of social media, the increasing popularity of taking selfies and using filters, we found it essential to examine the effect of these behaviors on the perception and attitude toward blepharoplasty.Aim: This article was conducted to assess participants' attitudes and perceptions toward taking selfies and using filters and their relation to blepharoplasty.Methods: This study was an observational cross-sectional study undertaken in Saudi Arabia. The study targeted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Several papers documented that taking selfies influences women to undergo cosmetic enhancement. For example, Dossari et al [19], reported that 50.6% and 47.6% of their subjects believed that taking a selfie and using filters may have significant roles in deciding to undergo blepharoplasty. This has been concurred by the paper of Aldosari [20], with both taking selfies and filters increasing the desire to get cosmetic procedures, particularly among women, while in a study by Alkarzae et al [14], dissatisfaction with self-appearance in selfies was the main reason of the sample population to undergo cosmetic enhancement procedures, wherein 5.8% had already undergone such procedures due to negative thoughts about their selfies.…”
Section: Discussionmentioning
confidence: 99%
“…Several papers documented that taking selfies influences women to undergo cosmetic enhancement. For example, Dossari et al [19], reported that 50.6% and 47.6% of their subjects believed that taking a selfie and using filters may have significant roles in deciding to undergo blepharoplasty. This has been concurred by the paper of Aldosari [20], with both taking selfies and filters increasing the desire to get cosmetic procedures, particularly among women, while in a study by Alkarzae et al [14], dissatisfaction with self-appearance in selfies was the main reason of the sample population to undergo cosmetic enhancement procedures, wherein 5.8% had already undergone such procedures due to negative thoughts about their selfies.…”
Section: Discussionmentioning
confidence: 99%